1972
DOI: 10.1042/bj1290241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic mercurials on mammalian pancreatic β-cells. Insulin release, glucose transport, glucose oxidation, membrane permeability and ultrastructure

Abstract: The effects of p-chloromercuribenzoic acid and chloromercuribenzene-p-sulphonic acid on pancreatic islets were studied in vitro. Obese-hyperglycaemic mice were used as the source of microdissected islets containing more than 90% beta-cells. p-Chloromercuribenzoic acid and chloromercuribenzene-p-sulphonic acid stimulated insulin release at concentrations of 0.01mm or above. This stimulation was significantly inhibited by the omission of Ca(2+) or the addition of adrenaline, diazoxide or 2,4-dinitrophenol. p-Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…Much smaller, if any, effects were noted in islets exposed to the other sulphydryl reagents tested. In view of the fact that chloromercuribenzene-p-sulphonic acid is by far the most potent initiator of insulin release (Bloom et al 1972;Hellman, Idahl, Lernmark, Sehlin & T&Ijedal, 1973a, b), the results support our hypothesis that organic mercurials stimulate insulin release through a direct action on the f8-cell plasma membrane leading to increased cation permeability (Bloom et al 1972).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Much smaller, if any, effects were noted in islets exposed to the other sulphydryl reagents tested. In view of the fact that chloromercuribenzene-p-sulphonic acid is by far the most potent initiator of insulin release (Bloom et al 1972;Hellman, Idahl, Lernmark, Sehlin & T&Ijedal, 1973a, b), the results support our hypothesis that organic mercurials stimulate insulin release through a direct action on the f8-cell plasma membrane leading to increased cation permeability (Bloom et al 1972).…”
Section: Discussionsupporting
confidence: 68%
“…The sucrose space was unaffected by all treatments except 1 mm chloromercuribenzene-p-sulphonic acid, which increased it (cf. Bloom, Hellman, Idahl, Lernmark, Sehlin & Taljedal, 1972). In addition to results obtained with each type of medium, the differences between parallel test and control incubations are given as mean values and s.E.…”
mentioning
confidence: 99%
“…105 In primary cultures of mouse pancreatic islet cells, mercuric chloride altered the intracellular calcium homeostasis and insulin secretion. 106,107 A report has shown that Minamata disease patients, who suffered from organic mercury poisoning from 1986 to 1994 (mean age: 63 years), had significantly elevated urine glucose levels. The authors suggested that increased mercury level in Minamata disease may enhance an incidence in diabetes.…”
Section: Mercurymentioning
confidence: 99%
“…Recently, increased oxidative DNA damage and serum redox status have been detected in individuals exposed to mercury (23). Moreover, previous in vitro studies have shown that HgCl 2 altered intracellular Ca 2ϩ homeostasis in pancreatic ␤-cells isolated from mouse islets (24) and decreased insulin secretion from secretion granules isolated from toadfish islets (25). It has also been shown that an increased incidence of diabetes existed in patients with documented Minamata disease (MeHg poisoning) in Japan (26).…”
mentioning
confidence: 96%